A time series analysis of the retail prices of beef in the province of Iloilo, 1974-1991 - Ealdama, Ma. Pamela G.
This study analyzed the monthly retail prices of beef in the Province of Iloilo from 1974 to 1991. The study showed that, on the average, the seasonality of beef prices does not vary widely during a given year. The highest seasonality experienced was only 0.60% above the average (average here refers to 100% or the average price for that year) and the lowest was 1.20% below the average seasonality. The seasonality of beef prices ranged from average to below average for the whole year round except during the months of July, August, and from December to February where it was slightly above average. The trend showed an upward movement of beef prices from 1974 to 1991, with a computed monthly average growth rate of 1.04%. The analysis of cyclical component showed that a downswing movement of beef prices was experienced from 1976 to 1978. In 1979 to 1984 the cyclical component of beef prices remained stable and lower than the average (trend). At the end of 1984, however, a cyclical upswing was observed, reaching its peak in 1985. A downswing movement was again observed fro 1986 until 1987. The year 1988 was observed to be the start of another upswing movement continuing until the end of 1991. It was observed that the highest irregularities in beef prices were experienced during 1984 and 1985. Irregularities were as high as 16% above the average (trend) during the said years. Beef prices are expected to increase to as high as P123.78 per kilo on 1994. The study, however, showed that the simple exponential technique fared poorly compared to the naïve model in forecasting the future prices of beef (1992-94). The simple exponential technique registered a mean square error of P5.86 higher than that of the naïve model which was P3.22.